Do People Perceive Products Differently when Buying for Self Versus for Others? Malleable Brand Personality in Gifting - Sussan, Fiona; Nakagawa, Hideyuki (European Scientific Journal, ESJ, 2023)
According to social identity theory, people behave differently in a social context than when they are by themselves because of social identity salience. Like people, brand personality changes depending on situations and context. There is lack of research investigating identity salience within the context of gifting and its subsequent impact on the perceived brand personality of a gift in different gifting situations. This paper proposes that in gifting situations of others, a social identity is activated which leads to change in the perceived brand personality of the same product purchased for self-gifting. Within the Japanese context, the hypothesis states that the excitement of brand personality dimension is more prominent in self-gifting than in gifting others, while competence and sincerity brand personalities are more prominent in gifting others than in self-gifting scenarios. To test these hypotheses, thirty-six brand personality traits (Aaker et al., 2001) of eight brands were evaluated by 251 respondents in Japan. Factor analysis and multiple regression results support the main hypotheses. The paper concludes with managerial implications and future research directions.